Can clinical and radiological findings predict surgery for lumbar disc herniation? A systematic literature review - White, Andrew P; Harrop, James; Dettori, Joseph R (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Objective or clinical question: What clinical and radiological findings in patients with lumbar-herniated nucleus pulposus can serve as predictors of surgical intervention?Methods: Articles published between January 1975 and August 2011 were systematically reviewed using Pubmed, Cochrane, National Guideline Clearinghouse Databases, and bibliographies of key articles. Each article was subject to quality rating and was analyzed by two independent reviewers.Results: From 123 citations, 21 underwent full-text review. Four studies met inclusion criteria. Only baseline disability as measured by the Roland Disability Index (RDI) or the Oswestry Disability Index (ODI) was consistently associated with a greater likelihood of having discectomy surgery across multiple studies. With the current literature, we were not able to find an association between surgery and several characteristics including smoking status, body mass index, neurological deficit, positive straight leg testing, and level of herniation.Conclusions: From the limited data available, it appears that individual radiographic and clinical features are not able to predict the likelihood of surgical intervention. Higher baseline disability measurements (Oswestry and Roland) did correlate, however, with surgical treatment.